Dexmedetomidine Protects against Airway Inflammation and Airway Remodeling in a Murine Model of Chronic Asthma through TLR4/NF-κB Signaling Pathway. (15th February 2023) - Zhou, Ying; Du, Xiyu; Wang, Qianyu; Xiao, Shilin; Zhi, Juan; Gao, Huibin; Yang, Dong
Abstract : Asthma is a common respiratory disease characterized by chronic airway inflammation. Dexmedetomidine (DEX), a highly selective α 2 adrenergic receptor agonist, has been shown to participate in regulating inflammatory states and thus exert organ protective actions. However, the potential of DEX in asthma is still unknown. This study is aimed at investigating the role of DEX in a mouse model of house dust mite- (HDM-) induced asthma and exploring its underlying mechanism. Here, we found that DEX treatment significantly ameliorated airway hyperresponsiveness, airway inflammation, and airway remodeling in the asthmatic mice, which were similar to the efficacy of the reference anti-inflammatory drug dexamethasone. In addition, DEX reversed the increased expression of toll-like receptor 4 (TLR4) and its downstream signaling adaptor molecule nuclear factor- κ B (NF- κ B) in the lung tissue of asthmatic mice. Furthermore, these protective effects of DEX were abolished by yohimbine, an α 2 adrenergic receptor antagonist. These results indicate that DEX is capable of ameliorating airway inflammation and remodeling in asthmatic mice, and this protective effect is associated with the inhibition of the TLR4/NF- κ B signaling pathway.